Labor market rigidities and the business cycle: Price vs. quantity restricting institutions - Mirko Abbritti; Sebastian Weber (Graduate Institute of International Studies, 2008)
We build a model that combines two types of labor market rigidities: real wage rigidities and labor market frictions. The model is used to analyze the implications of the interaction of different degrees and types of labor market rigidities for the business cycle by looking at three dimensions (i) the persistence of key economic variables; (ii) their volatility; (iii) the length, average duration and intensity of recessions and expansions. We find that real wage rigidities and labor market frictions, while often associated under the same category of labor market rigidities may have opposite effects on business cycle fluctuations. When the rigidity lies in the wage determination mechanism, real wages cannot fully adjust and shocks tend to be absorbed through changes in quantities. A higher degree of real wage rigidities thus amplifies the response of the real economy to shocks, shortens the duration of the business cycle but makes it more intense. When the rigidity lies in the labor market, it is more costly for firms to hire new workers and therefore unemployment does not vary as much, thus increasing inflation volatility and smoothening the response of the real economy to shocks. The cycle gets longer but less severe. Analyzing the interaction of institutions we show that these effects are reinforcing if institutions are substitutes - in the sense that countries with high labor market frictions tend to have low real wage rigidities and vice versa - while they are offsetting if institutions are complements. The findings from the model are supported when compared to the data of a range of OECD countries.
Keywords: 330; Konjunktur; Lohnrigidität; Reallohn; Arbeitsuche; Schätzung; OECD-Staaten